Effects of the Replacement of Dietary Fish Meal with Poultry By-Product Meal on Growth and Intestinal Health of Chinese Soft-Shelled Turtle (Pelodiscus sinensis) - Zongsheng Qiu; Qiyou Xu; Dazhang Xie; Jiantao Zhao; Fernando Y. Yamamoto; Hong Xu; Jianhua Zhao (Animals, 2023)
To investigate the effect of poultry by-product meal (PBM) replacing fish meal on the growth and intestinal health of Chinese soft-shelled turtle (Pelodiscus sinensis). Four experimental diets were prepared. Fish meal was replaced by 0 (control group, PBM0), 5% (PBM5), 10% (PBM10), and 15% (PBM15) PBM. Compared to the control group, final body weight, weight gain, and specific growth rate were significantly increased, while feed conversion rate decreased significantly in the PBM10 group (p < 0.05). The PBM15 group significantly increased the moisture content and significantly decreased the ash content of the turtles (p < 0.05). The PBM5 and PBM15 groups significantly decreased the whole-body crude lipid (p < 0.05). The serum glucose content increased significantly in the PBM10 group (p < 0.05). The liver malonaldehyde content significantly decreased in the PBM5 group and in the PBM10 group (p < 0.05). Liver glutamic-oxalacetic transaminase and intestinal pepsin activity were increased significantly in the PBM15 group (p < 0.05). The expression of the intestinal interleukin 10 (IL-10) gene was significantly down-regulated in the PBM10 group and the PBM15 group (p < 0.05), the expression of the intestinal interferon-γ (IFN-γ), interleukin-8 (IL-8), and liver toll-like receptor 4 (TLR4) and toll-like receptor 5 (TLR5) genes were significantly up-regulated in the PBM5 group (p < 0.05). In summary, poultry by-product meal can be used as a protein source to replace fish meal in turtle feed. Based on quadratic regression analysis, the optimal replacement ratio is 7.39%.